Implementasi Cluster Discount Di Hotel X - Natasha Lyanti Handoyo; Dewa Ayu Rai Sumariati; Ni Ketut Mareni (Pusat Penelitian dan Pengabdian Politeknik eLBajo Commodus, 2024)
The cluster discount program is implemented in all hotels under X International management to improve efficiency and profitability. This research aims to understand how the cluster discount is implemented at Hotel X. This study uses qualitative descriptive data analysis techniques. The data analysis process includes data collection, data reduction, data presentation, and drawing conclusions. Data were collected through interviews, observations, and documentation. The research results show that implementing the cluster discount program positively impacts reducing procurement costs, improving the efficiency of the procurement process, and better cost control. However, the program also has drawbacks, such as dependency on suppliers and implementation complexity. Recommendations for improvement include diversifying suppliers, increasing implementation efficiency, and strengthening control and supervision.The cluster discount program is an effective strategy to improve hotel efficiency and profitability. Further research is needed to evaluate the program's effectiveness in more detail and to optimize the process of selecting cluster areas and suppliers